Cultivating teacher resilience: The impact of transformational leadership and collaborative school culture amidst curriculum innovation - Hidayatun Nur; Gunawan Setiadi; Ahmad Hariyadi; Hisbulloh Als Mustofa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
Indonesia's Merdeka Curriculum introduces significant challenges for educators, making their professional well-being vital to successful educational reform. This study examines how principal leadership style and organizational culture impact primary school teachers' job satisfaction during this transition. This study employed a quantitative explanatory survey design. From a population of 123 certified civil-servant primary school teachers in Kudus Regency, a sample of 93 respondents was determined using the Slovin formula (5% margin of error) and selected through proportional stratified sampling. Data were collected via a closed-ended, five-point Likert-scale questionnaire (58 items) administered online, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Findings reveal both variables positively and significantly influence job satisfaction (R² = 0.541). Notably, organizational culture emerged as a stronger predictor (f² = 0.224) than leadership style (f² = 0.156), suggesting that shared collective values and peer collaboration foster critical emotional resilience among teachers. Ultimately, these results indicate that educational authorities must cultivate inclusive organizational cultures and humanistic leadership to mitigate occupational stress and sustain educators' psychological well-being. It is therefore recommended that education authorities prioritize culture-strengthening programs alongside transformational leadership training for principals, while future research should adopt longitudinal designs and examine factors beyond this model, such as compensation, workload, and intrinsic motivation.